The study of the investment policy formation of the enterprises as an important factor of their strategic development - Гринько, Павло Леонідович (Technology audit and production reserves, 2016)
Types, peculiarities of investments in the context of transition to an innovative model of economic growth of the country for the short term are specified. The state of the investment climate in Ukraine is studied, the ways of its improvement are defined, the effect of an investment policy on the formation of a corporate development plan is justified. The analysis of an investment activity in Ukraine revealed that macroeconomic indicators are still on the periphery of global investment flows. It was found that the main reasons of decrease in investment activity in Ukraine are: an unfavorable investment climate; inadequate legal framework; poor-quality arrangement of investment projects and programs, as well as their ineffectiveness; imperfection of investment instruments and investment market. Some suggestions concerning the formation of innovative and investment potential using the equity capital of companies are recommended. The principles of the investment policy of enterprises under the conditions of modern management paradigm are stated: the matching principle, the principle of interest and communication skills, the principle of flexibility and alternative, innovative principle, the principle of minimizing of the investment risk. The suggested in the research principles of investment policy make the investment policy of enterprises the tool for enhancement of efficiency of its functioning as a whole for the long term. This study contributes to the definition of the main directions of investment policies of enterprises of Ukraine.